The first chronic haemodialysis programme in Sri Lanka - Sheriff, M.H.R.; De Mel, W.C.P.; Ransi, W. (My University, 1985)
Although haemodialysis machines have been available in Sri Lanka since 1971, no chronic haemodialysis programme has been in existence. Even acute haemodialysis in a properly organized unit has been available only in November 1984 at the General Hospital, Colombo. The main reason for the lack of organized facility for chronic haemodialysis is the high cost of this form of therapy which the state can ill afford in the present economic situation in the country. Large sums of foreign exchange are spent in South India by our chronic renal failure patients, as our nearest and cheapest regional renal Unit of repute is at the Christian Medical College, Vellore. The patient and relatives are forced to stay on in India for long periods awaiting transplantation. The authors are aware of at least three patients who had come back to Sri Lanka with their own kidney machines and had subsequently died trying home dialysis without trained medical attention. We have launched a private Renal Unit project at the Borella private Hospitals ltd, Colombo 8 since May 1984. This unit has now expanded to a five bed station facility and operates on par with most European Renal Unit, standards. This paper describes the organization and working of the first chronic haemodialysis programme for Sri Lanka which is the stepping stone to an era of renal transplantation in Sri Lanka.